Pemberdayaan Peningkatan Kualitas Produk “Krupuk Rambak” Dalam Kearifan Lokal Untuk Meningkatkan Perekonomian di Kecamatan Toroh - Fariha Azzahra; Indah Rahayu; Dita Prameswari; Fani Fadila; Winarsih (LPPM AN Nuur, 2024)
Background: In the development of the home industry, it has experienced various kinds of problems which have hampered the process of developing micro businesses that have been run by the residents of Ngrandah Village. Meanwhile, Runtuwene (2017) explains that businesses that can survive in the market competitively, improving quality and productivity are priorities for every line of the company. However, people who have a cracker rambak micro business in Ngrandah Village have not fully focused on their business because they are busy and have limitations in managing and understanding how to manage their micro business. Method: Activities are carried out in several stages, namely first, the observation stage looking for problems faced by partners, the design stage looking at community conditions. Second, the implementation stage takes the form of outreach to partners so that the business develops well. Results: The activity provides material about the quality of products that will be managed and marketed by rambak cracker businesses so that their products can attract consumers by paying attention to clean production and safer packaging. The material is also about various kinds of marketplace and social media applications by assisting partners to create application accounts and assisting with techniques for operating these applications. Conclusion: Community service activities in the outreach program for partners who own rambak cracker businesses. Counseling and training were carried out smoothly and participants were enthusiastic about these activities.